Bulbophyllum gedangense (Orchidaceae, Epidendroideae, Malaxideae), a new species from Tibet, China - Luo, Yan; Deng, Jian-Ping; Peng, Yu-Lan; Yan, Li-Chun; Li, Jian-Wu (Phytotaxa, 2020)
Bulbophyllum gedangense (Orchidaceae), a new species from Tibet, China, is described and illustrated. It is morphologically similar to B. psychoon and B. levinei, but differs from them by having longer scapes, smaller flowers, sepals subequal in length, ovate dorsal sepal with obtuse apex, obliquely triangular-ovate lateral sepals with acute apex, ovate petals with entire margins and rounded apex.